Optimal Design of a High-Speed Single-Phase Flux Reversal Motor of Air Blower - A.Rahman, Nurul Ameera; Jenal , Mahyuzie (Evolution in Electrical and Electronic Engineering, 2023)
This paper described the optimal design of a single-phase high-speed flux reversal motor (FRM) for air blower application. Based on the literature, FRM is an electrical machine with a simple and reliable rotor structure which is significant for high-speed applications. The FRM efficiency can be boosted by using the full inner stator’s surface. Many previous research has shown the development of the FRM with various designs and numbers of rotor and stator slots, which have influenced the size and performance of the motor. For a high-speed application, a three-phase FRM with several salient pole designs was constructed, resulting in a low torque value with a high cogging torque. Therefore, a high-speed single-phase FRM with a modular rotor design was proposed in order to determine the best design for the motor in an air blower application. In this thesis, the performance of both motors was analyzed using FEM to reduce the cogging torque value as well as the flux path, which can reduce losses while increasing efficiency. The operating principle of the motor has been investigated and validated by the flux linkage, torque, power, and speed characteristics. The motors are also set to rotate in only one direction, making them suitable for unidirectional rotation applications such as air blowers. The optimal design of a high-speed single-phase FRM with modular rotor design is a better-suited approach as a result of this study.